1996
DOI: 10.1139/z96-203
|View full text |Cite
|
Sign up to set email alerts
|

Are avian ectoparasites more numerous in nest boxes with old nest material?

Abstract: Researchers may reduce the numbers of haematophagous ectoparasites in nest boxes of cavity-nesting birds by removing old nests from boxes and, as a result, eliminate an important selective pressure that could influence the results from nest-box studies of birds. We recorded the numbers of parasites in tree swallow (Tachycineta bicolor) boxes in which we manipulated the presence, amount, and quality of old nests. Bird fleas (Ceratophyllus idius) were more numerous in boxes with old nests, and there was a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 19 publications
2
60
0
Order By: Relevance
“…It seems that determining the costs of using nest sites with old nests related to the potential increase of predation cannot be appropriately evaluated in nestbox studies, because the boxes themselves are primarily aimed at improving the safety of the birds nesting there. Besides this, potential predator pressure was often completely eliminated in studies conducted to date by the techniques used in hanging boxes (on smooth metal poles) and protecting them with predatory guards, making access very difficult (Rendell & Verbeek 1996a, Utsey & Hepp 1997, Blem et al 1999). This may be why no differences were found in the breeding success of birds using boxes with old nest material and those using cleaned nestboxes (cf Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that determining the costs of using nest sites with old nests related to the potential increase of predation cannot be appropriately evaluated in nestbox studies, because the boxes themselves are primarily aimed at improving the safety of the birds nesting there. Besides this, potential predator pressure was often completely eliminated in studies conducted to date by the techniques used in hanging boxes (on smooth metal poles) and protecting them with predatory guards, making access very difficult (Rendell & Verbeek 1996a, Utsey & Hepp 1997, Blem et al 1999). This may be why no differences were found in the breeding success of birds using boxes with old nest material and those using cleaned nestboxes (cf Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Fleas overwinter most often as cocoons in old nest material, emerge in early spring, and very frequently wait for a bird host at the hole entrance (Humphries 1968, du Feu 1982. Mites may occur in old nest material also (Rendell & Verbeek 1996a), although clear data on their abundance in nest sites with/without old nest material are rare (Table 4). Flies and their larvae appear only after the nest sites are occupied, although Loye & Carrol (1998) suggested that fly imagines also remained in close proximity to sites used by birds, as well as the flies, in the previous season.…”
Section: Presence Of Ectoparasites and Other Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…For the time that the original nests were treated (around 30 minutes), a fresh substitute nest was introduced into the nest-box (these nests had been collected in previous seasons after being abandoned prior to laying and kept frozen at -20 ºC until use). This treatment ensured that experimental nests did not contain live arthropods when placed in the nest-box (Rendell and Verbeek 1996), although some arthropods may colonize the nest material after the treatment. To avoid the loss of water during the heat-treatment, the nests were placed into a hermetic plastic container.…”
Section: Experimental Reduction Of Ectoparasites Protocolmentioning
confidence: 99%
“…Thus, it is likely that time constraints (and, to a lesser extent, the lack of availability of empty nestboxes) deter the birds from moving in search of a new nest-site despite the accumulation of debris and the presence of ectoparasites (see more below), which can have detrimental effects on nestling condition (Richner et al 1993, Rendell & Verbeek 1996aMazgajski 2007). The costs of nest-site switching may offset costs associated with the reuse of soiled cavities as has been shown experimentally in other multi-brooded passerines (Stanback & Rockwell 2003).…”
Section: Discussionmentioning
confidence: 99%